PERAN HEPCIDIN DAN VITAMIN D DALAM PATOFISIOLOGI ANEMIA PADA ANAK DENGAN PENYAKIT GINJAL KRONIK - Lestari, Hertanti Indah (Sriwijaya Journal of Medicine, 2020)
In patients with Chronic Kidney Disease (CKD), renal function in maintaining the homeostasis of various metabolic systems of the body is impaired, one of which is the production of erythropoietin hormones. Anemia is a frequent complication of the CKD and contributes to the increasing morbidity and mortality of the patients. Diagnosis or treatment of anemia in PGK is still a challenge due to multifacorial. Hepcidin, a peptide that has been known as an acute phase protein, plays an important role in the regulation of iron metabolism. Hepcidin is known to have a correlation with ferritin, a parameter of anemia screening which is commonly examined during this time. In addition to the role of pathophysiology anemia in CKD, hepcidin is currently widely researched because it is suspected to contribute also to the pathophysiology of bone mineral disorders in PGK. Current research shows that the concentration of vitamin D is inversely proportional to the concentration of hepcidin and is positively associated with the concentration of hemoglobin and iron. The latest report invitro and invivo support the existence of the interaction between vitamin D and anemia in patients with PGK through the role of Hepcidin. Keywords: chronic kidney disease, anemia, hepcidin, vitamin D